2012
DOI: 10.4028/www.scientific.net/kem.507.67
|View full text |Cite
|
Sign up to set email alerts
|

High Voltage Electrophoretic Deposition of Aligned Nanoforests for Scalable Nanomanufacturing of Electrochemical Energy Storage Devices

Abstract: High voltage electrophoretic deposition (HVEPD) has been used to obtain forests of aligned multi-walled carbon nanotubes (MWCNTs) on long strips of flexible, conductive substrates. Successful design and integration of a continuous HVEPD setup has enabled scalable fabrication of electrodes for electrochemical energy storage. The mechanism of continuous HVEPD has been investigated to ensure appropriate alignment. Well-aligned forests of MWCNTs were obtained using a conductive holding layer which helped reduce in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…1a,b) without the use of PMMA or other conventional polymer stabilization routes. Utilizing SWCNTs suspended in surfactantfree polar solvents [6][7][8], electrophoretic processing is scalable, inexpensive [9], capable of integration with manufacturing platforms, such as roll-to-roll or industrial systems [12][13][14], and overcomes the limitations of other SWCNT electrophoretic approaches which utilize surfactant [10,11]. We specifically observe stabilization of 3-D graphene foams that are found to maintain pristine optical response and significantly improved electrical response in comparison to PMMA-stabilized materials.…”
Section: Introductionmentioning
confidence: 82%
“…1a,b) without the use of PMMA or other conventional polymer stabilization routes. Utilizing SWCNTs suspended in surfactantfree polar solvents [6][7][8], electrophoretic processing is scalable, inexpensive [9], capable of integration with manufacturing platforms, such as roll-to-roll or industrial systems [12][13][14], and overcomes the limitations of other SWCNT electrophoretic approaches which utilize surfactant [10,11]. We specifically observe stabilization of 3-D graphene foams that are found to maintain pristine optical response and significantly improved electrical response in comparison to PMMA-stabilized materials.…”
Section: Introductionmentioning
confidence: 82%
“…However, the negative charges of the IPA‐dispersed CNTs are often found insufficient to support their effective deposition using EPD. In order to improve the deposition characteristics of the dispersed CNTs, charging agents such as surfactants and charging salts are often used. The metal salts dissolved in the dispersion medium typically provide metal ions with positive charges to the CNTs.…”
Section: Working Mechanism — Electrophoretic Depositionmentioning
confidence: 99%
“…The existing reports of superhydrophobic coatings produced by EPD usually employ spherical particles with additional nonconductive coatings . Previous works by our team have demonstrated the ability to control the orientation of electrophoretically deposited 1D nanomaterials such as CNT and MnO 2 nanorods. The technology has also been employed to align highly crystalline MnO 2 nanorods as high‐performance redox capacitors with excellent durability along with demonstration of a continuous deposition process to scale up the fabrication .…”
Section: Introductionmentioning
confidence: 99%
“…Among the publications related to nanoparticles coating via EPD, only a few provide the information of continuous deposition. Santhanagopalan et al reported the continuous deposition of CNTs on long strips of metal foil; a pump with a flow rate of eight mL/min was used to replenish the CNT dispersion [10]. Three research groups, led by Jiang [11,12], Li [13], and Huang [14], respectively, reported the coating of graphene oxide on carbon fibers and fiber tows continuously via EPD.…”
Section: Introductionmentioning
confidence: 99%